Phylogenomics of Severe Acute Respiratory Syndrome Coronavirus 2 in Emergency Shelters for People Experiencing Homelessness. (29th January 2022) - Casto, Amanda M; Rogers, Julia H; Link, Amy C; Boeckh, Michael; Jackson, Michael L; Uyeki, Timothy M; Englund, Janet A; Starita, Lea M; Chu, Helen Y
Abstract: Background: Residents and staff of emergency shelters for people experiencing homelessness (PEH) are at high risk of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The importance of shelter-related transmission of SARS-CoV-2 in this population remains unclear. It is also unknown whether there is significant spread of shelter-related viruses into surrounding communities. Methods: We analyzed genome sequence data for 28 SARS-CoV-2-positive specimens collected from 8 shelters in King County, Washington between March and October, 2020. Results: We identified at least 12 separate SARS-CoV-2 introduction events into these 8 shelters and estimated that 57% (16 of 28) of the examined cases of SARS-CoV-2 infection were the result of intrashelter transmission. However, we identified just a few SARS-CoV-2 specimens from Washington that were possible descendants of shelter viruses. Conclusions: Our data suggest that SARS-CoV-2 spread in shelters is common, but we did not observe evidence of widespread transmission of shelter-related viruses into the general population. Abstract : Using genomic data, we estimate that 28 cases of SARS-CoV-2 infection in 8 shelters in King County, Washington were the result of at least 12 introduction events and that at least 16 of these cases resulted from intrashelter viral transmission.